Near‐vent chemical processes in a hydrothermal plume: Insights from an integrated study of the Endeavour segment. (21st April 2017) - Coogan, L. A.; Attar, A.; Mihaly, S. F.; Jeffries, M; Pope, M.
Abstract: The Endeavour segment of the Juan de Fuca mid‐ocean ridge is one of the best studied ridge segments and has recently been instrumented as part of Ocean Networks Canada's NEPTUNE cabled observatory. Here we investigate the interaction between high‐temperature vent fluids and the overlying water column. A new tow‐yo survey found that the average temperature anomaly in the neutrally buoyant plume was ∼0.043°C. The water column temperature and light attenuation anomalies correlate linearly in some areas of the plume but in other areas there is a low light attenuation anomaly relative to the temperature anomaly. This temperature excess is interpreted to reflect heat input through (particle‐poor) diffuse flow. If this is correct, about half of the heat flux along the Endeavour segment comes from diffuse flow. Sediment trap and push core data show that the mass accumulation rate of the hydrothermal component of the sediments decreases rapidly with distance from the major vent fields. Large changes in the composition of the hydrothermal component of the sediments also occur with distance from the vent fields. The composition of the sediments indicates (i) sulfides precipitate early and accumulate most rapidly close to the vents with a preferential order of element removal from the plume of Cd > Ag > Cu > Co ∼ Fe; (ii) barite is deposited somewhat further from the vents. Strontium and Pb appear to be strongly incorporated in barite and/or other sulfate minerals; (iii) at most a few percent of the mass of these "insoluble" elements that is vented gets deposited within 1.5 km of the vents. Key Points: Temperature and light attenuation anomalies in the water column suggest ∼50% of the hydrothermal heat flux is from diffuse flow Hydrothermal sediment accumulation rates drop dramatically within hundreds of meters of the major vent fields Hydrothermal sediment composition changes substantially with distance from the vents